Secure Cloud Storage Privacy-Preserving In Public Auditing (International Journal of Innovative Research in Computer Science & Technology, 2023)
Cloud computing is a technology that is  both efficient and cost-effective, thanks to its low mainte nance requirements. This paper implemented a approach is  used to share group resources across cloud users. Regretta bly, as a result of the frequent differences in participation,  the issue of sharing information in a multi-owner manner  while also preserving privacy and information from a trusted  cloud continues to be a challenging one. During the course  we put into place a safe method of data sharing among mul tiple owners using the Diffe- Hellman algorithm that are  cloud-based and applicable to rotating groups. By leveraging  techniques like as group signature and dynamic broadcast  encryption, any user of the cloud has the ability to anony mously share data with other users. In the meanwhile, the  number of users whose access has been revoked does not  have any impact on the storage overhead or encryption com putation costs associated with our system. In addition, em ploy rigorous proofs to investigate the scheme's level of  safety, and conduct tests to verify the scheme's usefulness.
Keywords: Cloud computing; Encryption methods; Dynamic Groups Privacy; Shared Data; Revocation Data